Respostas

2014-07-08T23:01:52-03:00
a) -x²+12x-36=0
Δ = b2 - 4.a.c 
Δ = 122 - 4 . -1 . -36 
Δ = 144 - 4. -1 . -36 
Δ = 0
x = (-b +- √Δ)/2a
x' = (-12 + √0)/2.-1         x'' = (-12 - √0)/2.-1
x' = -12 / -2                    x'' = -12 / -2
x' = 6                             x'' = 6

b) x²-5x-2=0
Δ = b² - 4.a.c 
Δ = (-5)² - 4 . 1 . -2 
Δ = 25 - 4. 1 . -2 
Δ = 33

x = (-b +- √Δ)/2a
x' = (--5 + √33)/2.1        x'' = (--5 - √33)/2.1
x' = 10,744 / 2              x'' = -0,744 / 2
x' 
 5,372                     x''  -0,372

c) 3x²+15x=0
x(3x+15)=0
x=0                            3x+15=0
                                  3x=-15
                                  x=-15/3
                                  x=-5
2 4 2